👤

a) [tex] \frac{1}{4} [/tex]x-6=[tex] \frac{1}{3} [/tex](2-x)+[tex] \frac{1}{3} [/tex]
b)2(x-3)+[tex] \frac{11}{2} [/tex]
c)[tex] \frac{5}{6} [/tex](x-4)+x=[tex] \frac{1}{3} [/tex](x+2)-3
d)[tex] \frac{3}{8} [/tex](x+2)+[tex] \frac{x}{4} [/tex]=[tex] \frac{5}{6} [/tex](x-3)+2


Răspuns :

x-6=(2-x)+
x/4-6=2/3-x/3+1/3
x/4+x/3=6+2/3+1/3
(3x+4x)/12=(6·12+2·4+1·4)/12
7x/12=(72+8+4)/12
7x=84
x=84/7=12
b)2(x-3)+
2x-6+11/2=0
2x=6-11/2
2x=(12-11)/2
2x=1/2
4x=1
x=1/4
c)(x-4)+x=(x+2)-3
5x/6-20/6+x=x/3+2/3-3
5x/6+x-x/3=20/6+2/3-3
(5x+6x-2x)/12=(20+4-18)/6
9x=6
x=6/9=2/3
d)(x+2)+=(x-3)+2
3x/8+6/8+x/4=5x/6-15/6+2
3x/8+x/4-5x/6=-6/8-15/6+2
(9x+6x-20x)/24=(-18-60+48)/24
-5x=-30    (-1)
x=30/5
x=6